LEGAL DUE TO THE FOUNDATIONS ASSETS TRANSFER BEFORE MAKING ADJUSTMENTS TO THE ARTICLES OF ASSOCIATION - Mauida, Nia; Rokhim, Abdul (International Significance of Notary, 2022)
The existence of foundations before the enactment of Government Regulation of the Republic of Indonesia Number 2 of 2013 concerning Amendments to Government Regulation of the Republic of Indonesia Number 63 of 2008 concerning the Implementation of the Law on Foundations has not been uniform regarding governancecits stance. Foundation establishment is still based on custom, doctrine and jurisprudence. For foundations that do not have the status of a legal entity, they can obtainlegal entity status by adjusting its articles of association by submitting an application to the Minister of Law and Human Rights no later than 1 (one) year from the date Law Number 28 of 2004 concerning Foundations came into effect. Foundations that were established before the enactment of Government Regulation Number 2 of 2013 and have not adjusted their articles of association may not transfer foundation assets.In this study, the type of normative juridical research uses a statutory approach, a comparative approach and a conceptual approach. The results of the study show that: first, the position of foundation assets before the enactment of Government Regulation Number 2 of 2013 is based on custom, jurisprudence and doctrine. While the position of foundation assets after the enactment of Government Regulation Number 2 of 2013 tercantum in Article 9 Paragraph (1) of the Law on Foundations which states that as initial assets the founder of the foundation is required to separate his assets and then hand them over to the foundation. Second, the legal consequences of transferring Foundation assets before making adjustments to the articles of association based on Government Regulation of the Republic of Indonesia Number 2 of 2013 refers to the provisions of article 71 paragraph (4) of the Law on Foundations, which states that a Foundation that does not adjust its Articles of Association cannot use the word " Foundation” in front of the name because legally, the status of a legal entity is not recognized formally, the consequence is that the transfer of foundation assets that is carried out becomes null and void (neitig van rechtswege) and is not recognized as a transfer of foundation assetsin a mannerlegal. Keywords: Legal Consequences, Transfer, Foundation Assets, Articles of Association